(untitled) - Klemela, Jussi (Hoboken, N.J., 2008)
Smoothing of Multivariate Data provides an illustrative and hands-on approach to the multivariate aspects of density estimation, emphasizing the use of visualization tools. Rather than outlining the theoretical concepts of classification and regression, this book focuses on the procedures for estimating a multivariate distribution via smoothing
Keywords: Smoothing (Statistics),Analysis of variance,Estimation theory